Correlation of rpoB Mutations with Minimal Inhibitory Concentration of Rifampin and Rifabutin in Mycobacterium tuberculosis in an HIV/AIDS Endemic Setting, South Africa - Rukasha, Ivy; Said, Halima M.; Omar, Shaheed V.; Koornhof, Hendrik; Dreyer, Andries W.; Musekiwa, Alfred; Moultrie, Harry; Hoosen, Anwar A.; Kaplan, Gilla; Fallows, Dorothy; Ismail, Nazir (Frontiers in Microbiology, 2016)
Abstract Treatment of tuberculosis (TB) and HIV co-infection is often complicated by drug-drug interactions between anti-mycobacterial and anti-retroviral (ARV) agents. Rifabutin (RFB) is an alternative to rifampin (RIF) for TB regimens and is recommended for HIV patients concurrently receiving protease inhibitors because of reduced induction of CYP3A4. This study sought to determine the proportion of RFB susceptible isolates among RIF resistant strains in a high HIV prevalence setting in South Africa. In addition, the study explored the association between rpoB mutations and minimum inhibitory concentration (MIC) levels of RIF and RFB. A total of 189 multidrug resistant (MDR) M. tuberculosis isolates from the Centre for Tuberculosis (CTB) repository were analyzed. The MICs were determined using a Sensititre MYCOTB system and the rpoB gene was sequenced. Of the 189 MDR isolates, 138 (73%) showed resistance to both RIF and RFB, while 51 (27%) isolates were resistant to RIF but RFB susceptibility. S531L was the most frequent rpoB mutation in 105/189 (56%) isolates, followed by H526Y in 27/189 (14%) isolates. Resistance to both RIF and RFB was found predominantly in association with mutations S531L (91/105, 87%), H526Y (20/27, 74%), and H526D (15/19, 79%), while D516V (15/17, 88%) and L533P (3/4, 75%) were found in RFB susceptible isolates. This study has shown that up to 27% of MDR-TB patients in South Africa may benefit from a treatment regimen that includes RFB.